Electron properties of semiconductor surface studied by the electroreflectance spectroscopy method - Gentsar, P.A.; Vlasenko, A.I.; Kudryavtsev, A.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Relations between the Keldysh-Franz oscillations with electron parameters of semiconductor materials were used to derive qualitative data for homoepitaxial films n-GaAs (100) from their electroreflectance spectra. The spectra were measured using the Shottky barrier method at the temperature 300 K and non-polarized light from the range 1.3-1.65 eV in vicinity of E0 transition (Г8v → Г6с). The spectral data enabled to get values of the following electron parameters: the energy of the electron transition, electrooptical energy, surface electric field, phenomenological parameter of widening, charge carrier relaxation time by energy, relative phase factor, extension of the wave function oscillation and the value of electron mobility. The obtained values are in a good agreement with known data for structurally perfect n-GaAs with the electron concentration n = 10¹⁷ – 10¹⁸ cm⁻³ .